Joined supernumerary mandibular teeth in the premolar region: Report of a Hungarian archeological case - Gy. Szabó; G. Kocsis S.; E. Molnár (Dental Anthropology Association, 2009)
Supernumerary teeth are those that are additional to the normal complement. They may occur in any region of the dental arch and have been reported in both the primary and the permanent dentitions. The etiology of supernumerary teeth is still not clearly understood, but several theories have been suggested for their occurrence. The investigated material were the remains from the Bácsalmás-Óalmás burial site (from the 16th-17th centuries), where 472 skeletons were excavated from 1993 to 2003. For the purpose of this study, the dentitions of 164 adult individuals were examined. The examination was carried out using macromorphological methods, radiographic analysis and a dial caliper were applied. This paper describes a supernumerary tooth of an adult female skeleton. On the labial surface of the first mandibular premolar an extra tooth was observed. Radiographic examination of the fused teeth indicated that the crown of the premolar had fused incompletely with the crown of the extra tooth. The position of the extra tooth could have been the result of gemination of the tooth germ or the elaboration of the buccal cingulum. The cranium of the examined individual showed some mongoloid morphologic features, too. Our presumption about the formation of the supernumerary tooth may have contributed to the theories of the occurrence of supernumeraries. The sporadic occurrence of this anomaly was reported in recent and archaeological skeletal collections. This study showed that multiple permanent dental formation was present in past Hungarian populations, representing a contribution to the history of dental anomalies.